Estimates for weighted eigenvalues of fourth-order elliptic operator with variable coefficients - He-Jun Sun (Український математичний журнал, 2011)
We investigate the Dirichlet weighted eigenvalue problem for a fourth-order elliptic operator with variable coefficients in a bounded domain in Rⁿ. We establish a sharp inequality for its eigenvalues. It yields an estimate for the upper bound of the (k+1)-th eigenvalue in terms of the first k eigenvalues. Moreover, we also obtain estimates for some special cases of this problem. In particular, our results generalize the Wang -Xia inequality (J. Funct. Anal. - 2007. - 245) for the clamped plate problem to a fourth-order elliptic operator with variable coefficients. Дослiджено задачу Дiрiхле про зваженi власнi значення для елiптичного оператора четвертого порядку iз змiнними коефiцiєнтами в обмеженiй областi iз Rⁿ. Встановлено точну нерiвнiсть для її власних значень, з якої випливає оцiнка для верхньої межi (k+1)-го власного значення через першi k власних значень. Також отримано оцiнки для цiєї задачi у деяких окремих випадках. Зокрема, нашi результати узагальнюють нерiвнiсть Ванга – Ксi (J. Funct. Anal. – 2007. – 245) для затиснутої пластини на випадок елiптичного оператора четвертого порядку iз змiнними коефiцiєнтами